Preparation of ZrO2-coated NiO powder using surface-induced coating - Moon, JW; Lee, HL; Kim, JD; Kim, GD; Lee, DA; Lee, HW (ELSEVIER SCIENCE BV, 1999)
Zirconia-coated NiO powder was prepared by a newly developed surface-induced coating using thermal hydrolysis of Zr(NO3)(2) . 6H(2)O in a mixed solvent of alcohol and water. Amorphous zirconium hydroxide was uniformly coated on the surface of NiO powder with the thickness of 20 nm. The ZrO2 coating layer was crystallized to tetragonal ZrO2 with the size of 40-60 nm at 900 degrees C. The coated NiO powder containing 15 vol.% ZrO2, was found to have a similar isoelectric point to that of the ZrO2. The surface-induced ZrO2 coating was a more efficient method for the prevention of Ni sintering than the mechanical mixing. (C) 1999 Elsevier Science B.V, All rights reserved.
Keywords: AQUEOUS SALT-SOLUTIONS; ALCOHOL